薄膜式醣晶片的發展及應用 - 劉詠儀; Lao, Weng-I (2009)
生物體內細胞表面醣類分子與蛋白質間相互作用具有很多重要的?能，包括調控細胞分化、細胞附著、免疫反應、蛋白質運輸、腫瘤細胞轉移及微生物感染等重要的生理?能。這些?能皆透過特定的凝集素、抗體或蛋白質與細胞表面上醣蛋白或醣脂質末端的醣類分子發生交互作用所引發的。過去發展?多技術用於蛋白質與醣類間交互作用的研究上，例如酵素結合免疫吸附分析、平衡透析、表面等離子共振技術、等溫滴定微量熱法、親和性層析及醣類晶片。其中最為成?的技術則是醣類晶片，它的原理是透過疏水作用力、biotin與streptavidin作用或共價鍵等將醣類分子固定在玻璃、金屬或矽等材質的表面。本研究目的是建立薄膜式醣類晶片平台來偵測凝集素、蛋白質和病毒與醣類間作用的關係。本論文使用了88種biotin-PAA(polyacrylamide)-sugar，分別測試透過streptavidin、抗biotin抗體或直接固定在薄膜上，研究中使用了三種不同的薄膜：包括西方墨點法所用的轉漬膜PVDF、DNA晶片常用的帶正電尼龍膜及適用於蛋白質晶片的UltraBind薄膜；結果的觀察則是透過標記有鹼性磷酸酶的凝集素或抗體來進行。本研究結果顯示biotin-PAA-sugar能成?地透過streptavidin固定在UltraBind薄膜上，而最適用於本薄膜的填塞緩衝液則是含有酪蛋白的TBST裡。透過18個已知凝集素及4個抗醣類抗體測試，結果分析符合過去研究的結果。再來是應用這平台分析人類和禽類的感冒病毒在晶片上的結合圖譜，我們測試了臨床分離的流感病毒16株B型、1株A型及2株禽類的H6N1，結果發現禽類流感病毒主要與alpha 2-3鏈結的唾液酸結合，而人類流感則是與alpha 2-6鏈結的唾液酸結合為主，此外我們也發現了毒性較高的禽類流感病毒與醣類結合能力較強，因此推測禽類感冒病毒其致病能力與結合醣類能力有關聯。 Protein-carbohydrate interactions involved in many important biological processes including cell differentiation adhesion immune response protein trafficking and tumor metastasis All of these functions occur through the interaction between glycans on glycoprotein or glycolipid displayed on cell surfaces with specific lectins antibodies or proteins Many techniques have been developed to study protein-carbohydrate interactions including enzyme-linked lectin sorbent assay (ELLSA) equilibrium dialysis surface plasmon resonance isothermal titration calorimetry frontal affinity chromatography (FAC) and carbohydrate microarray Carbohydrate microarray which glycans are immobilized on the surface of glass or silicon through hydrophobic interactions biotin-streptavidin interactions or covalent bonding is one of the most successful approaches Here we established a carbohydrate membrane array platform to explore protein-carbohydrate interaction of lectins proteins and microorganisms Eighty-eight biotin conjugated polyacrylamide (PAA) based glycan epitopes were immobilized directly or through streptavidin/anti-biotin antibody on three membranes (PVDF nylon membrane or UltraBind membrane) The binding signal was observed by alkaline phosphatase conjugated on lectins or antibodies It showed that PAA based glycan epitopes could be immobilized on UltraBind membranes through streptacidin and casein in Tris buffer saline (TBS) with 0 05% Tween 20 was the best buffer for blocking The binding profiles of eighteen known lectins and four anti-Lewis sugar antibodies were analyzed and the results were comparable to literature In addition this platform was applied to investigate the carbohydrate binding profiles of influenza virus The profiles of twenty clinical isolates of influenza B viruse and avian influenza viruse (H6N1) were examined and the results showed that avian viruse selectively bound with alpha 2-3 linked sialosides (sialylated glycans) and human viruse selectively bound with alpha 2-6 linked sialosides respectively Furthermore the binding strength of high virulence avian influenza virus was obviously stronger than low one The finding has opened a new direction for inspecting the relationship between the carbohydrate epitopes and the avian flu